2002
DOI: 10.1038/sj.eye.6700035
|View full text |Cite
|
Sign up to set email alerts
|

A short term study of the additive effect of timolol and brimonidine on intraocular pressure

Abstract: A short term study of A Topalkara the additive effect of timolol and brimonidine on intraocular pressure AbstractPurpose To evaluate the additive ocular hypotensive effect of the combination of brimonidine and timolol on intraocular pressure (IOP) reduction in patients with glaucoma. Methods This was a prospective, randomized, double-masked, crossover study in 20 patients with primary open angle glaucoma (POAG) on therapy receiving timolol maleate 0.5% twice daily, with IOP greater than or equal to 22 mmHg in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…[3] In another short-term 3-week study found that the mean IOP was significantly reduced by an average of 5.44 ± 1.98 mmHg compared with baseline value with the use of the fixed combination. [4] Thus the results of our study are in congruence with these studies further supporting the additive IOP lowering effect of the brimonidine-timolol fixed combination. Data from the Early Manifest Glaucoma Trial have shown that even 1 mm Hg of additional IOP lowering reduces the risk of glaucoma progression by 10%.…”
Section: Discussionsupporting
confidence: 88%
“…[3] In another short-term 3-week study found that the mean IOP was significantly reduced by an average of 5.44 ± 1.98 mmHg compared with baseline value with the use of the fixed combination. [4] Thus the results of our study are in congruence with these studies further supporting the additive IOP lowering effect of the brimonidine-timolol fixed combination. Data from the Early Manifest Glaucoma Trial have shown that even 1 mm Hg of additional IOP lowering reduces the risk of glaucoma progression by 10%.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6][7] Approved for use in 1977, timolol given once or twice daily lowers IOP in POAG and OH by reducing the production of aqueous humour. [8][9][10] Latanoprost, the first prostaglandin F 2a analogue to be commercially available in Europe and the US, has been shown to lower IOP more effectively than timolol when administered once daily.…”
mentioning
confidence: 99%
“…Another similar study (Arici et al 2002) evaluated the effect of adjunctive brimonidine in timolol-treated subjects over a longer time period of 3 weeks. IOP reduction of 5.1 mmHg (21.2%), 5.9 mmHg (24.5%), and 5.7 mmHg (23.6%) at weeks 1, 2, and 3 respectively was found.…”
Section: Concomitant Brimonidine and Timolol Therapymentioning
confidence: 99%